حماية وأمن شبكات الواي فاي ضد الاختراق والتطفل بالتطبيق على كلية كسلا التقانية - د أحمد محمد نور عجيل; د. غفاري حسن حاج حمد (White Nile Journal for Studies and Research, 2025)
This study present solutions to the problems of Hacking, and Intrusion on wireless network specially (wi-fi) networks which became using in spread way in companies , institutions and a large residential compounds. The study took more care of Illegal Hacking of Wireless Networks and complete the legal Users of applications and services of these networks, control and regulation of Wi-Fi connections. The study aimed to determine the weakness points in Access to (wi-fi) devices by using MAC address filtering in addition to strong passwords. The study used analytical description methodology, deductive and application methodology to study the Hacking of (wi=fi) devices. The study used algorithmic in designing and models for the networks of (wi-fi) devices in common use (D-link & Linksys Devices) in application. The important results which arrived by this study, design secure Access model for Wi-Fi networks. and applicant packets to deny Access the Intrusions Access to Wi-Fi networks. The study recommended to the important using of (wi-fi) devices which have a big capacity to filters physical address (MAC Address) and connecting more then one (wi=fi) to ensure the controlling process and to increasing the numbers of users on a wireless network. The study also recommended for the important to one Device per user policy and complicate the password, change it periodically, trained the users to keep the password, and activating IP Address verification to enhance the security features of the wireless network. Keywords: (wi-fi) networks , wireless networks , safe arriving , passwords , physical address(MAC address)